Behavior of Foundations on Reinforced Sabkha Soil A Numerical Study - Sadek, Lamia; Bahloul, Khaled M. M. (International Journal of Scientific Research in Civil Engineering, 2020)
The aim of this research is to investigate numerically the behavior of strip footings resting on Sabkha soil reinforced using two methods. Firstly, using a layer of compacted sand reinforced with random distributed fibers beneath footing. Secondly, using a layer of compacted sand reinforced with geogrids. The benefit of mentioned two methods on the improvement of strip footings bearing capacity and decreasing the settlement was investigated using a finite element computer program Plaxis 2D ver. 8.6. It was found that using two methods increases bearing capacity of strip footings significantly specially using first method (fiber reinforced sand layer). It was observed also that the settlement decreased for the same stress values.
Keywords: Strip Footings; Sabkha Soil; Bearing Capacity; Fibers; Geogrids; finite element; Plaxis